How local health departments use wastewater surveillance data for public health planning and intervention in New York State - Shailla Raymond; Mila Neyra; Dustin T. Hill; Ainsley Maclachlan; Jordan McGuire; Matthew Mahaney; Nicole Pulido; Bhavneet Walia; Nan Yang; Yifan Zhu; Yiquan Zhou; David A. Larsen (BMC Public Health)
Abstract Wastewater surveillance presents a novel data stream for local health departments to understand infectious disease risk in their communities. We conducted a survey of local health departments in New York State regarding their knowledge, attitudes, and practices toward wastewater surveillance of SARS-CoV-2. We further conducted in-depth interviews with a number of local health departments to identify specific use cases of wastewater surveillance data. Almost all survey respondents used wastewater surveillance data and reported advantages to wastewater surveillance data, with the most common use being the tracking of disease trends, followed by monitoring variants, detecting diseases early, and assessing public health interventions. Some counties were sharing wastewater surveillance data with hospitals, which use the data for planning purposes. Public health communication was the most commonly reported action taken from wastewater surveillance data. These findings highlight that local health departments generally have favorable attitudes toward wastewater surveillance. However, there is a need for continued training and support for local health departments to apply these data in their practice.